Effect of CYP3A4 genetic polymorphisms on the genotoxicity of 4, 4′-methylene-bis(2-chloroaniline)-exposed workers. Issue 1 (27th September 2016) - Wang, Chung-Ching; Chen, Wei-Liang; Hsiung, Chia-Ni; Chiang, Sheng-Ta; Wang, Ying-Chuan; Loh, Ching-Hui; Lin, I-Shen; Chen, Hong-I; Liou, Saou-Hsing
Abstract : Objectives: We investigated the relationship between 4, 4'-methylene-bis(2-chloroaniline) (MBOCA) exposure and micronucleus (MN) frequency, and how this association was affected by genetic polymorphism of the cytochrome P450 enzyme (CYP3A4). Methods: We divided the study population into an exposed group (n=44 with total urine MBOCA ≥20 μg/g creatinine) and a control group (n=47 with total urine MBOCA <20 μg/g creatinine). Lymphocyte MN frequency (MNF) and micronucleated cell (MNC) frequency were measured by the cytokinesis-block MN assay method. MNF reported as the number of micronuclei in binucleated cells per 1000 cells, and MNC reported as the number of binucleated cells with the presence of MN per 1000 cells. CYP3A4 alleles were measured by PCR-based restriction fragment length polymorphism (PCR-RFLP). Results: The mean MNF (6.11 vs 4.46 MN/1000 cells, p<0.001) and MNC (5.75 vs 4.15 MN/1000 cells, p<0.001) in the exposed workers was significantly higher than that in the controls. The CYP3A4 polymorphism A/A+A/G influenced the difference in the mean MNF (5.97 vs 4.38 MN/1000 cells, p<0.001) and MNC (5.60 vs 4.15 MN/1000 cells, p<0.001) between the MBOCA-exposed and control groups. After adjusting risk factors, the MNF level in the MBOCA-exposed workers was 0.520 MN cells/1000 cells (p<0.001) higher than the control group among the CYP3A4 A/A+A/G genotype. Similarly, the MNC level in the MBOCA-exposed workers was 0.593 MN/1000 cells (p<0.001) higher than the control group among the CYP3A4 A/A+A/G genotype. However, the difference in adjusted MNF and MNC between the exposed and control groups was not significant for the CYP3A4 polymorphism with the G/G genotype. Conclusions: We recommend that lymphocytes MNF and MNC are good indicators to evaluate MBOCA genotoxicity. Individuals with the CYP3A4 polymorphism A/A and A/G genotypes appear to be more susceptible to MBOCA genotoxicity.